PENGARUH GAYA KEPEMIMPINAN, KEMAMPUAN KERJA, KARAKTERISTIK PEKERJAAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. NUSA KAHYANGAN ASRI GIANYAR - Ni Putu Megiyani; I Gusti Ngurah Eka Teja Kusuma; I Gede Rihayana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
Human resources in an organization or company are the main cogs and determinants of the success of a company organization.Increased employee productivity will bring progress for the company to be able to survive in a competitive business environment in the era of globalization with a leader who can carry out tasks or management functions. the ability to influence and move other people to work to achieve organizational goals, while job characteristics are a follow-up to the job design process. This study aims to test and obtain empirical evidence of the influence of leadership style, work ability, job characteristics on employee work productivity at PT. Nusa Kahyangan Asri Gianyar. The population of this study were production employees at PT.Nusa Kahyangan Asri Gianyar. The sample in this study were 45 employees based on the sampling method. The results showed that leadership style, work ability, job characteristics had a significant positive effect on the work productivity of the employees of PT. Nusa Kahyangan Asri Gianyar. Further research can develop this research by using other variables in theory to have an influence on work productivity